Evaluating the Efficacy of Monobloc Distraction in the Crouzon-Pfeiffer Craniofacial Deformity Using Geometric Morphometrics. Issue 2 (February 2017) - Visser, Richard; Ruff, Clifford F.; Angullia, Freida; Ponniah, Allan J. T.; Jeelani, N. U. Owase; Britto, Jonathan A.; Koudstaal, Maarten J.; Dunaway, David J.
Abstract : Background: Crouzon-Pfeiffer syndrome is caused by mutations predominantly in the FGFR2 gene leading to syndromic craniosynostosis and midfacial hypoplasia. Monobloc distraction aims to correct both functional and aesthetic disharmony as a result of midfacial hypoplasia. This study evaluates the corrective effects and effectiveness of monobloc distraction in Crouzon-Pfeiffer patients. Methods: Preoperative and postoperative scans were collected from 20 Crouzon and two Pfeiffer patients aged 7 to 20 years. Fifty-six normal skulls were used as a control group. Geometric morphometrics using 52 frontofacial landmarks were used to analyze the normal skull and preoperative and postoperative patient skulls. Color maps were created to visualize differences among the average normal, preoperative, and postoperative Crouzon-Pfeiffer patients. Results: In the studied patient population, monobloc distraction with the use of an external distractor advanced the upper half of the midface more than the lower half of the midface. There was an anteroinferior rotation in the monobloc segment. The zygomatic arch length improved on average to 88 and 90 percent of normal (right and left, respectively), whereas globe protrusion was corrected from 134 percent to 84 percent and from 131 percent to 87 percent of normal (right and left, respectively) in the studied patient population. Compared with a normal skull, the maxillary region remained retruded. Conclusions: The advancement achieved by monobloc distraction is effective in the upper half of the midface; the lower half of the midface is advanced but remains retruded in comparison with the normal population. The midface is rotated anteroinferiorly. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.